The solution for the given equations x + 3y = 5 and x - 3y = -1 are x=2 and y=1.
Step-by-step explanation:
The given is,
......................................(1)
....................................(2)
Step:1
By elimination method,
Subtracting Equations (1) and (2),
![x+3y=5](https://tex.z-dn.net/?f=x%2B3y%3D5)
![x-3y=-1](https://tex.z-dn.net/?f=x-3y%3D-1)
( - )
(
) + (
) = (
)
= 6
= 1
Step:2
Substitute the value of y in equation (1),
![x+3y=5](https://tex.z-dn.net/?f=x%2B3y%3D5)
+ ( 3 × 1 ) = 5
= 5-3
= 2
Step:3
Check for Solution,
Substitute the values of x and y in Eqn (1),
![x+3y=5](https://tex.z-dn.net/?f=x%2B3y%3D5)
2 + ( 3 × 1 ) = 5
5 = 5
Result:
The solution for the given equations x + 3y = 5 and x - 3y = -1 are x=2 and y=1, by elimination method.
16.24 divided by 0.14 equals 116 i hope this helps if not sorry :)
1 and 1/4 cups shall fill each bottle
Hope this helps!!!<3
Can I get Brainliest?!?!